Like dandelion dust. - Pepper, Barry; Sorvino, Mira; Levering, Kate; Cotton, Maxwell Perry; Hauser, Cole (Beverly Hills, Calif : Twentieth Century Fox Home Entertainment, 2011)
Wendy and Rip Porter are a working-class couple fighting to regain custody of Joey, the young son Wendy gave up for adoption when Rip went to prison seven years earlier. But Joey's adoptive parents will stop at nothing to ensure to ensure that the small boy stays in the only home he's ever known.
Based on the book by Karen Kingsbury
Originally produced as a motion picture in 2009
Special features : Audio commentary with director Jon Gunn and producers Kerry David and Bobby Downes; Like Dandelion Dust comes to life; Deleted scenes with Director Commentary; Extended Scenes; Adoption Stories with Author Karen Kingsbury and Producer Kevin Downes
Keywords: Kingsbury, Karen -- Film adaptations; Birthparents -- Drama; Adoptive parents -- Drama